2000
DOI: 10.1097/00000539-200010000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Optison (FS069) Disrupts the Blood-Brain Barrier in Rats

Abstract: Optison is a new echocardiographic contrast agent, designed for IV injection, that is very useful in delineating cardiac structures during ultrasound examination. Because Optison could be a valuable adjunct in the diagnosis and evaluation of congenital heart disease, this study was undertaken to assess its effects on the blood-brain barrier when introduced directly in the cerebral circulation, as might occur with some congenital lesions. In this study, Sprague-Dawley rats were anesthetized, and Optison, at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Disruption of the blood-brain barrier may occur in rats after intravenous injection of ultrasound contrast media [17,18].…”
Section: Experimental Findingsmentioning
confidence: 99%
“…Disruption of the blood-brain barrier may occur in rats after intravenous injection of ultrasound contrast media [17,18].…”
Section: Experimental Findingsmentioning
confidence: 99%
“…Since previous studies showed destruction of the blood-brain barrier (BBB) several hours after injection of Optison into the carotid artery 14 or insonation after intravenous injection of Optison, 15 we carefully evaluated the safety aspect of the present gene transfer method. We first evaluated the change in body weight, tissue damage by hematoxylin and eosin (HE) staining, and destruction of the BBB by microangiography using albumin-fluorescein isothiocyanate (FITCalbumin), 16 as the microbubble-enhanced ultrasound Figure 4 Local gene expression produced by plasmid DNA transfer using microbubble-enhanced ultrasound as assessed by luciferase expression.…”
Section: Safety Evaluationmentioning
confidence: 99%
“…In these studies, Doppler-based nonlinear imaging technologies with higher receiving frequencies seem to be superior to grey scale harmonic imaging [69]. In theory, when using high MI imaging, the direct contrast-enhanced insonation of the brain without the skull (which reduces the actual energy that has an effect on the tissue) could be harmful because of cavitation and capillary rupture [80,81,82,83]. …”
Section: Examination Of the Microcirculation – Brain Perfusion Imagingmentioning
confidence: 99%